Morphological, histochemical and morphometric study of the myotomal muscle tissue of the pacu (Piaractus mesopotamicus Holmberg 1887: Serrasalminae, Characidae, Teleostei) - Dal Pai, V; Dal Pai-Silva, M.; Carvalho, E. D.; Fujihara, C. Y.; Gregorio, E. A.; Curi, P. R. (Blackwell Wissenschafts Verlag Gmbh, 2000)
Histochemical, ultrastructural and morphometric methods were used to study growth patterns of red, pink and white muscle fibres and their relation to body weight and total length in the fast-growing freshwater fish Piaractus mesopotamicus Holmberg. The correlations amongst body weight, body length and diameter of red, pink and white fibres were low. From 10-15 to 40 50 cm, body weight increased 102.7 times, while the diameter of each type of fibro increased by factors of 0.94, 0.74 and 0.70, respectively. Muscle fibres revealed different morphological and histochemical stages of maturation. The frequencies of < 20 mu-m fibres of red, pink and white muscle tissue in the youngest and oldest classes were 64.5 and 11.0, 38.2 and 7.7 and 24.0 and 1.4%, respectively. In 30-40 cm fish, the frequency of < 20 mu-m fibres in the red and pink tissue was 24.5 and 25.5%, while in the white tissue it was 11.5%. During sexual maturity (40-50 cm), the recruitment of < 20 pm fibres in white muscle was 1.4%. Muscle fibres of this species showed continuous growth by both hyperplastic and hypertrophic mechanisms, and hyperplasia was particularly active in the juvenile phase.